Teaching Playwriting to University Level in Indonesia: Using Pictures to Develop a One-act Play - Herlin Putri (Journal of English Language and Culture, 2017)
As a subject offered at the university level, playwriting can only elicit a lukewarm response from the Indonesian students compared to the other genres such as poetry and prose. Mainly due to lack of imagination and unfamiliarity with the elements of drama, the students feel discouraged at the very onset. This study endeavours to explore these barriers and suggest an approach that can help the students in overcoming them as proved by certain teaching experiments conducted in a playwriting class at English Department, University of Indonesia. A method that the present study heartily endorses is using pictures to help students develop a one-act play. The results show that carefully selected pictures can spark and hone students’ imagination to develop more vivid characters and advance an interesting conflict-based plot. It also creates a dynamic learning process in which students’ imagination and creativity are given a massive chance to develop. The findings of this study contribute to teachers who teach creative writing as well as general skills of English. Keywords: Creative writing, playwriting, picture stimulus, elements of drama, imaginatio